High-performance flexible lead-free piezo-antiferroelectric based on NaNbO3/PDMS composites for energy harvesting application - Sumang, Rattiphorn; Charoonsuk, Thitirat; Vittayakorn, Naratip; Panpho, Phakakorn (My University, 2024)
To bring the rapidly advancing technology of energy harvesters into commercial use, further development is required for devices that can enhance output performance, flexibility, ease of fabrication, and low cost. A hybrid concept is a promising method. It combines between the piezoelectric nanogenerator (PENG) and the triboelectric nanogenerator (TENG) to provide a high-performance nanogenerator. This study introduced a high-performance hybrid PENG and TENG device that operates using a NN-BNT/PDMS composite film. The NN-BNT/PDMS composite based nanogenerators were fabricated with varying NN-BNT content. Then, dielectric test and electrical properties were investigated. Adding NN-BNT into the PDMS composite film resulted in a higher dielectric constant compared to pure PDMS, leading to increase of electrical output. Under the optimal condition of a 3 wt%. NN-BNT composite based hybrid nanogenerator, the electrical output was significantly enhanced, reaching 40 V, 0.95 μA/cm2, and 200 μW/cm2 compared to pure PDMS. This nanogenerator further used to the charging of a capacitor to a voltage of around 1 V within 5 s and also powered multiple LEDs. The successful development of this highly efficient NN-BNT/PDMS composite film-based hybrid concept sheds light on energy harvesting devices.
Keywords: Hybrid nanogenerators; PDMS; Relaxor antiferroelectric; Triboelectric